a RIVIEW: SINTESIS BIODIESEL DENGAN KATALIS HETEROGEN DARI CANGKANG HEWAN MOLLUSCA - Mukhlash Imaduddin; Samik Samik (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2023)
Energy is a very important need in human life. Most of the energy needs that humans need are supplied from non-renewable natural resources such as oil, natural gas and coal. The solution given is to replace it with biodiesel. Biodiesel is an alternative energy based on plants and animals. Sources of vegetable oil can be obtained from rubber seeds and cooking oil. Rubber seeds contain about 40-50%-w vegetable oil with the dominant fatty acid composition being oleic acid and linoleic acid, while the rest are palmitic acid, stearic acid, arachidic acid and other fatty acids. Catalysts derived from several shells showed that the yield value of the highest shellfish was in green mussels with a yield of 90.1% with a reaction temperature of 65oC for 4 hours with a catalyst weight of 5% of the weight of biodiesel.. Keywords: Calcination, Transesterification, Mollusca